CHST1 as a prognostic-related biomarker in gastric cancer correlating with immune infiltration - Long Gui; Jin-hao Yu; Jia-nan Tan; Guang-yu Zhong; Yong-xue Wang; Lin Zhong; Jiao-jiao Su; Dong Hou; Bin Yang; Fang-hai Han; Sheng-ning Zhou (Heliyon)
Carbohydrate sulfotransferase (CHST) is a Golgi membrane-associated enzyme with potential as a cancer diagnostic marker. In this study, we obtained the transcriptional profile and corresponding clinical information of CHST1 in gastric cancer (GC) tissues and normal tissues from The Cancer Genome Atlas database. Our functional experiments have demonstrated that CHST1 enhances the proliferation and metastasis of GC cells, both in vitro and in vivo. Furthermore, we constructed a co-expression network of CHST1 and explored its relationship with clinicopathological features, the tumor microenvironment, and immune infiltration through bioinformatics analysis. Finally, relevant drugs that inhibit CHST1 in GC were predicted using the drug susceptibility database (CellMiner) and Cancer Immunome Atlas. Overall, CHST1 may serve as a promising prognostic biomarker for GC, as it is linked to immune infiltration and facilitates GC cell proliferation and metastasis.